Prognostic value of systemic inflammation response index in cervical cancer: a meta-analysis - Xiaoxing Zhang; Dongmei Ni; Kai Zhu; Xieyan Yu (Future Science OA)
Background The value of systemic inflammation response index (SIRI) in predicting cervical cancer (CC) prognosis has been evaluated, but the conclusions were debated. By performing a meta-analysis, this study sought to establish the accurate prognostic relevance of SIRI for CC.Methods The study aimed to determine the effect of SIRI on predicting CC overall survival (OS) and progression-free survival (PFS) by HRs with 95%CIs.Results This work incorporated seven studies with 1271 patients enrolled. Based on our combined data, elevated SIRI exhibited remarkable relation to dismal OS (HR = 2.58, 95%CI = 1.75–3.79, p < 0.001) and worse PFS (HR = 1.88, 95%CI 1.33–2.66, p < 0.001) in CC. In addition, higher SIRI was significantly associated with advanced FIGO stage (OR = 1.71, 95%CI = 1.18–2.50, p = 0.005) and high-grade histology (OR = 1.63, 95%CI = 1.15–2.32, p = 0.006) of CC. Nonetheless, SIRI was not related to age, lymphovascular invasion (LVSI), tumor size, tumor invasion depth, pathological type, or lymph node (LN) metastasis.Conclusion This meta-analysis revealed that higher SIRI is significantly related to impaired OS and poor PFS of CC cases. Furthermore, higher SIRI is also significant correlated to advanced FIGO stage and poor tumor differentiation of CC.